Diagnosis and Treatment of Vaginal Discharge Syndromes in Community Practice Settings. (30th April 2020) - Hillier, Sharon L; Austin, Michele; Macio, Ingrid; Meyn, Leslie A; Badway, David; Beigi, Richard
Abstract: Background: Although vaginal symptoms are common, diagnosis of bacterial vaginosis (BV), vulvovaginal candidiasis (VVC), and Trichomonas vaginalis (TV) is not standardized. Diagnostic approaches and appropriateness of treatment were evaluated for women with symptoms of vaginitis who were seeking care at community practice sites. Methods: Three hundred three symptomatic women, across 8 University of Pittsburgh Medical Center–affiliated clinics, were evaluated per standard office-based practice. Four of 5 vaginal swabs (1 cryopreserved) were collected for a US Food and Drug Administration–authorized nucleic acid amplification test (NAAT) for vaginitis/vaginosis diagnosis; Nugent scoring (BV); yeast culture (VVC); and a second NAAT (for TV). Two hundred ninety women had evaluable samples. Medical record extraction facilitated verification of treatments prescribed within 7 days of the index visit and return visit frequency within 90 days. Results: Women had a mean age of 29.4 ± 6.5 years, 90% were not pregnant, 79% were of white race, and 38% reported vaginitis treatment within the past month. Point-of-care tests, including vaginal pH (15%), potassium hydroxide/whiff (21%), and wet mount microscopy (17%), were rarely performed. Of the 170 women having a laboratory-diagnosed cause of vaginitis, 81 (47%) received 1 or more inappropriate prescriptions. Of the 120 women without BV, TV, or VVC, 41 (34%) were prescribed antibiotics and/or antifungals. Among women without infectious vaginitis, return visits for vaginitis symptoms were more common among women treated empirically compared to those not receiving treatment (9/41 vs 5/79, P = .02). Conclusions: Within a community practice setting, 42% of women having vaginitis symptoms received inappropriate treatment. Women without infections who received empiric treatment were more likely have recurrent visits within 90 days. Clinical Trials Registration: NCT03151928. Abstract : Laboratory-confirmed bacterial vaginosis, yeast vulvovaginitis, and trichomoniasis were frequent in community-based settings, but clinic-based diagnosis was often inaccurate. Inappropriate therapy was prescribed to 42% of women; those without infections who were treated empirically were more likely to return in 90 days.